Computed tomographic and radiographic bronchial collapse may be a normal characteristic of forced expiration in dogs. Issue 5 (22nd May 2018) - Kim, Hyunryung; Kim, Young Joo; Lee, Hanbin; An, Taegeon; Yu, Jin; Yoon, Hyounglok; An, Gayeon; Jung, Jaihyun; Chang, Jinhwa; Chang, Dongwoo
Abstract: Tracheobronchomalacia has been diagnosed using radiography or bronchoscopy to confirm bronchial changes in luminal diameter during the respiratory cycle. However, studies in healthy humans suggest that some degree of bronchial collapse may be observed during the normal respiratory cycle. In this analytical study, the luminal diameter of the bronchus to each of the six pulmonary lobes and the mean percentage of expiratory collapse from end inspiratory, end expiratory, and two forced expiratory phases (10 and 15 ml/kg) were determined via computed tomography (CT) and radiography in 22 healthy Beagle dogs. The bronchial collapsibility was significantly greater during the forced expiration than the end expiration ( P  < 0.001); the same results were observed in dorsal and sagittal CT images and radiographs ( P  < 0.001). Median collapsibility values associated with 15 ml/kg forced expiratory collapse determined via cross‐sectional CT images were measured as 16.6–45.5% and differed according to the pulmonary lobe. Median collapsibilities on radiography with 15 ml/kg forced expiration were 57.8% and 62.1% in the right cranial lobe and right caudal lobe, respectively. In conclusion, bronchial diameter may change during the respiratory cycle, and some degree of reduction in bronchial diameter may be an incidental finding in healthy dogs. More rigorous criteria are needed with regards to bronchial collapsibility during normal respiration for the diagnosis of bronchomalacia in order to avoid false‐positive diagnoses.